The assessment of cultural psychology and linguistically diverse students: an exploratory study on the practices of counselors - Talavera Pérez, Isabel; Guzmán Rosquete, Remedios (Revista Complutense de Educación, 2017)
Owing to the migration flows that have occurred in the last decade in many countries, European education policies have shown a growing concern for how educational institutions respond to culturally and linguistically diverse (CLD) students. In this regard, various reports and studies have highlighted the over-identification of CLD students in special education classrooms. This has contributed to questioning the validity of diagnostic practices and their instruments in identifying the specific educational needs of a CLD student. In Spain no published studies are available about these diagnostic practices used by professionals. The main purpose of this study was to explore the psychological assessment practices of school counsellors when they have to identify the needs of CLD pupils in primary and secondary education. The sample consisted of 64 counsellors belonging to 13 psychoeducational teams in Tenerife, working in centres with CLD students. An ad hoc questionnaire consisting of 21 questions grouped into four dimensions was designed: I) Professional experience and sociodemographic variables, II) Psychological assessment factors, III) Selection and use of diagnostic instruments and IV) Evaluation of linguistic competence and the use of interpreters. Although there are not specific instructions in our country on how to assessing CLD students, results showed that these proffesionals take into account differential factors while doing so, especially those related to the acculturation level of the students. Different use of assessment tests were noticed, depending on the student was fluent in spanish language or not, although less than half of them resorted to translators to evaluate the non spanish speaking students.
Keywords: Foreing pupil; assessment; evaluation; school counsellors; special education